Introductory Statistics - Mann, Prem S. (USA : John Wiley and Sons, 1992)
Introduction, Organizing data, Numerical descriptive measures, Probability, Discrete random variables and their probability distributions, Sampling distributions, Estimation of the mean and prortion, Chi-square tests, Simple linear regression...
Keywords: Statistics; Statistics